Implementasi Pelatihan Metode Baca Gali Alkitab (BGA) Berbasis Genre Kitab bagi Anak Asrama GBI Rock Sikakap - Hutahaean, Hasahatan; Mangentang, Matheus; Wibowo, Moses; Pakpahan, Rugun (IAKN TORAJA, 2022)
Abstract: Reading activities, and digging into the Bible are believed to be able to form a strong, fresh, and swift spirituality amid the congregation. Both categorical children, adolescents, adults, and the elderly because the Bible is the Word of God that can transform people in the work of the Holy Spirit. This study aims to find the right method to give to the younger generation is facing an era that is constantly advancing, and changing but in that, but it has a good and bad impact at the same time. Of course, it is bad if faith is not solid. The activity was carried out by the workshop method by providing Bible Reading (BGA) training to GBI Rock dormitory children in South Pagai, Mentawai Islands. The result seems to arouse the curiosity of the younger generation in reading and meditating on God's Word. Together with this passion, faith with good quality, bibles, and is believed to be swift to walk the future. Abstrak: Kegiatan membaca, menggali Alkitab diyakini mampu membentuk kerohanian yang kuat, segar dan sigap di tengah-tengah jemaat. Baik kategorial anak, remaja, dewasa hingga warga lansia sebab Alkitab adalah Firman Allah yang sanggup mengubah manusia dalam karya Roh Kudus. Penelitian ini bertujuan menemukan metode yang tepat untuk diberikan kepada generasi muda dalam menghadapi zaman yang terus-menerus maju, berubah namun memberi dampak baik dan buruk sekaligus. Tentu berdampak buruk jika iman tidak kokoh. Kegiatan dilakukan dengan metode workshop dengan memberikan pelatihan Baca Gali Alkitab (BGA) kepada anak asrama GBI Rock di Pagai Selatan, Kepulauan Mentawai. Hasilnya tampak menggugah keingintahuan generasi muda dalam membaca dan merenungkan Firman Tuhan. Bersama dengan gairah tersebut tumbuh juga iman dengan kualitas yang baik, biblis dan diyakini sigap untuk menapaki masa depan.